Increased risk of acute stroke among patients with severe COVID‐19: a multicenter study and meta‐analysis. (16th October 2020) - Siepmann, T.; Sedghi, A.; Simon, E.; Winzer, S.; Barlinn, J.; de With, K.; Mirow, L.; Wolz, M.; Gruenewald, T.; Schroettner, P.; von Bonin, S.; Pallesen, L.‐P.; et al.
Abstract : Background and purpose: Recent observations linked coronavirus disease 2019 (COVID‐19) to thromboembolic complications possibly mediated by increased blood coagulability and inflammatory endothelial impairment. We aimed to define the risk of acute stroke in patients with severe and non‐severe COVID‐19. Methods: We performed an observational, multicenter cohort study in four participating hospitals in Saxony, Germany to characterize consecutive patients with laboratory‐confirmed COVID‐19 who experienced acute stroke during hospitalization. Furthermore, we conducted a systematic review using PubMed/MEDLINE, Embase, Cochrane Library and bibliographies of identified papers following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines including data from observational studies of acute stroke in COVID‐19 patients. Data were extracted by two independent reviewers and pooled with multicenter data to calculate risk ratios (RRs) and 95% confidence intervals (95% CIs) for acute stroke related to COVID‐19 severity using a random‐effects model. Between‐study heterogeneity was assessed using Cochran's Q and I 2 statistics. International Prospective Register of Systematic Reviews registration number: CRD42020187194. Results: Of 165 patients hospitalized for COVID‐19 (49.1% males, median age = 67 years [57–79 years], 72.1% severe or critical) included in the multicenter study, overall stroke rate was 4.2% (95% CI: 1.9–8.7). Systematic literature search identified two observational studies involving 576 patients that were eligible for meta‐analysis. Amongst 741 pooled COVID‐19 patients, overall stroke rate was 2.9% (95% CI: 1.9–4.5). Risk of acute stroke was increased for patients with severe compared to non‐severe COVID‐19 (RR = 4.18, 95% CI: 1.7–10.25; P = 0.002) with no evidence of heterogeneity ( I 2 = 0%, P = 0.82). Conclusions: Synthesized analysis of data from our multicenter study and previously published cohorts indicates that severity of COVID‐19 is associated with an increased risk of acute stroke. Abstract : Our pooled analyis of observational multicenter data from Germany and published data from cohorts in Italy and China suggests that patients with severe course of COVID‐19 have an increased risk of acute stroke. This observation emphasizes the necessity of clinical neurological monitoring in patients infected with SARS‐CoV‐2 and warrants further investigation of the underlying pathophysiology.